12 Grieving during COVID-19: exploring the lived experiences of people bereaved during the first two waves of the pandemic. (30th January 2023) - Mazzaschi, Francesca; Barawi, Kali; Torren-Burton, Anna; Sutton, Eileen; Wakefield, Donna; Gilbert, Emma; Goss, Silvia; Longo, Mirella; Seddon, Kathy; Nelson, Annmarie; Byrne, Anthony; Selman, Lucy; et al.
Abstract : Introduction: The COVID-19 pandemic has had a huge impact on all aspects of life. The high number of deaths and bereavements increased demand on already stretched services, whilst the unique circumstances caused by enforced social distancing meant that people bereaved at this time faced many additional challenges and potentially problematic grief trajectories. Aims: To explore in depth people's lived experiences of bereavement during the Covid-19 pandemic, their adaptation and coping during this time, and the effect of informal and formal sources of bereavement support . Methods: Semi-structured longitudinal telephone interviews were conducted with people bereaved during the first 10 months of the pandemic (March to December 2020), purposively sampled from a cohort of survey participants. Interview transcripts were analysed thematically. Results: 24 participants (19 female; 5 men) took part in a first interview and 15 in a follow up interview, approximately four months later. Five major themes were identified: End of life experiences; Funerals and memorialisation; Grieving and psychological impacts; Coping and adaptation and Sources of support. Many challenges relating to the pandemic context were identified, including restrictions to end of life and memorialisation arrangements, dealing with personal affairs, and lack of support. Such experiences negatively impacted individual grieving and wellbeing, in particular feelings of isolation and guilt surrounding lack of contact with the deceased. Participants experienced difficulties accessing services, and sometimes received support that was not appropriate for their particular situations and needs. Despite these difficulties, some people demonstrated remarkable resilience, and ability to cope and find meaning. Conclusions: People bereaved in the COVID-19 pandemic have navigated grief and bereavement through exceptionally challenging circumstances, often lacking the informal and formal support needed to help them cope. Impact: These insights can be used to help improve the care and support provided to bereaved people throughout their bereavement journeys.